Effectiveness of Teaching the Pronunciation of Inflection Through Analytic-Linguistic Approach - Sharma, Lok Raj (International Research Journal of MMC, 2021)
The principal objective of the research study is to examine the effectiveness of teaching the pronunciation of inflection in English words through the analytic-linguistic approach. The researcher followed a pre-experiment research design, especially one- group- pretest- posttest- design, which included a pretest measure followed by a treatment and a posttest for a single group after the treatment or intervention. A set of fifty multiple choice test items was administered to the sample of 21 bachelor first year education students studying major English at Makawanpur Multiple Campus, Hetauda, Nepal in the Academic Year 2019-2020. The researcher adopted the census method also known as a statistical enumeration method wherein each and every student in the population was selected for eliciting the primary data. The result showed there was a statistically significant difference between the pretest mean score (M=20.190, SD=14.169 and N=21) and the posttest mean score (M= 25.619, SD=14.844 and N=21) of the students. The statistics of (df) =20, p< .05, the observed t-value= 4.38 and the table t-value = 2.086 at 0.05 significance level of the test showed that teaching the pronunciation of inflection through the analytic-linguistic approach was effective among the students at this campus. This study contributes to the existing body of the pronunciation of English words by highlighting that the same spelling functioning as the inflection of the English words has different pronunciation. It is shown through presentations.